1962
DOI: 10.1103/physrev.128.800
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Protons from Deuteron Stripping Reactions with a Zero Orbital Angular Momentum Transfer

Abstract: Angular dependence of the polarization of protons from the / = 0 stripping reactions, Al 27 (^)Al 28 g . s . + ist and Si 28 (^,^)Si 29 g . s . has been measured at a deuteron energy of 15 MeV. Polarization changes the sign at angles close to each minimum of the angular distribution, remaining the same in the angular region corresponding to each stripping peak. The magnitude of polarization is large (20 to 30%) near the angles at which the sign change takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Data taken with lighter elements, such as the aluminum and silicon data of Isoya et al, 11 have shown only limited agreement with the derivative rule. Isoya et al observed polarization sign changes at angles close to the stripping minima but not at the stripping peaks.…”
Section: B (Dp) Polarization Measurementsmentioning
confidence: 96%
See 2 more Smart Citations
“…Data taken with lighter elements, such as the aluminum and silicon data of Isoya et al, 11 have shown only limited agreement with the derivative rule. Isoya et al observed polarization sign changes at angles close to the stripping minima but not at the stripping peaks.…”
Section: B (Dp) Polarization Measurementsmentioning
confidence: 96%
“…Previousp olarization measurements have yielded polarizations larger than the 33% limit, 5-9 and nonzero polarizations for ^=0 transfers. [9][10][11][12] One means of accounting for the above discrepancies is to include additional terms in the optical-model potentials which affect the spins of the incident and outgoing particles directly. The effects of a spin-orbit term in the optical-model potential seen by the proton, for example, may be visualized by considering outgoing protons with opposite spin projections, which therefore see potential wells of different depths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation